(untitled) (Journal of Agriculture & Rural Development, 2008)
An investigation was conducted at Mithapukur and Razarhat upazila under Rangpur and Kurigram districts, respectively to know the requirements, utilization pattern and repayment system of credit and its effect on modern rice cultivation. A total number of 120 rice growers who obtained credit from Rajshahi Krishi Unnayan Bank (RKUB) and Grameen Bank (GB) were interviewed. Another 60 farmers who did not take credit from other sources were also studied. The findings disclosed that the client farmers of RKUB and GB used about 78 and 72 percent credit, respectively for Boro rice production and the rest was used for consumption purpose. The cost of credit of RKUB and GB was Tk. 463 and Tk. 20, respectively. The RKUB farmers had to pay Tk. 252 as entertainment cost. The GB credit users borne 1.13 times higher production cost compared to RKUB users for Boro rice cultivation. Loan users achieved 1.21 times higher rice yield compared to loan non-users. The analysis of resources use efficiency revealed that both credit users and non-users rice growers had failed to use inputs efficiently, either the production inputs were overused or underused. Unavailability of credit and weekly instalment system of repaying loan were the main constraints faced by 38 percent RKUB and 53 percent GB credit users. Small farmers were found to avoid cumbersome procedure of obtaining loan from the institutional sources and they felt better to borrow loan from NGOs. Key words: RKUB, GB, MV Boro rice, credit and farmers.